Hard carbon negative electrode material and preparation method and application thereof
Hard carbon anode materials are produced by hot-pressing and annealing hard carbon and specific inorganic carbon materials, which solves the problems of low hardness and poor structural stability of hard carbon materials, and achieves efficient electrochemical performance improvement and cycle life extension.
Patent Information
- Application Number
- CN202411507173.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-21
AI Technical Summary
The irregular microstructure of hard carbon materials leads to low hardness and poor structural stability, making it difficult to maintain a long cycle life and high Coulomb efficiency, and is prone to deformation or rupture during rolling, affecting electrochemical performance.
The hard carbon anode material is prepared by mixing hard carbon with an inorganic carbon material with specific compressive strength, hot pressing, and annealing under an inert gas. This method induces the rearrangement of internal atoms of hard carbon, changes the growth orientation and size of crystallites, increases hardness, and forms a strong interface through physical cross-linking and functional group reaction to improve electrochemical performance.
Improve the hardness and electrochemical properties of hard carbon negative materials, enhance structural stability, extend the cycle life of the battery, and reduce the preparation cost.
Smart Images

Figure CN119340325A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery energy storage, and in particular to a hard carbon negative electrode material and a preparation method and application thereof. Background Art
[0002] As a typical amorphous carbon material, hard carbon contains a large number of curved graphite microcrystalline layers and amorphous regions, has a large interlayer spacing (more than 0.37nm) and abundant defect sites. As a sodium storage material, it has a long and reversible low potential (<0.1V) charging / discharging platform. However, the irregular microstructure of hard carbon materials leads to a small van der Waals force between its carbon layers, making its hardness low and its structural stability poor. During the charging and discharging process, the structure of the material is easily damaged, making it difficult to maintain a long cycle life and high coulombic efficiency. In addition, when using hard carbon materials to prepare pole pieces, during the rolling process, the hard carbon materials will be more easily deformed or even broken when subjected to external pressure, which seriously affects their electrochemical performance.
[0003] Although the hardness of hard carbon can be improved to a certain extent by constructing nanostructures through template methods and promoting the formation of more fine grains in the hard carbon structure, or by changing the electronic structure and chemical bond strength of hard carbon through element doping and other means to enhance the hardness of hard carbon, these methods usually have problems such as complex processes, high costs, and poor results. Therefore, it is of great significance to develop a simple, efficient and low-cost method to increase the hardness of hard carbon while maintaining excellent electrochemical properties. Summary of the invention
[0004] Based on this, it is necessary to provide a hard carbon negative electrode material and its preparation method and application to address the above problems; the preparation method described in the present invention is simple, efficient and low-cost, and the prepared hard carbon negative electrode material not only has high hardness but also has excellent electrochemical properties.
[0005] A method for preparing a hard carbon negative electrode material comprises the following steps:
[0006] Mixing hard carbon and inorganic carbon material and subjecting them to hot pressing treatment, wherein the compressive strength of the inorganic carbon material is 200MPa-1000MPa, and the mass of the inorganic carbon material is 0.1%-1% of the mass of the hard carbon;
[0007] The product after the hot pressing treatment is annealed under an inert gas to obtain a hard carbon negative electrode material, wherein the grain size La of the hard carbon negative electrode material is greater than or equal to 12 nm.
[0008] In one embodiment, the grain size La of the hard carbon negative electrode material is 12nm-22nm;
[0009] And / or, the Young's modulus of the inorganic carbon material is 50 GPa-700 GPa;
[0010] And / or, the particle size of the inorganic carbon material is 10nm-100nm;
[0011] And / or, the specific surface area of the inorganic carbon material is 800m 2 / g-2000m 2 / g.
[0012] In one embodiment, the inorganic carbon material is selected from at least one of carbon fiber, graphene fiber, carbon nanotube, graphene or carbon ceramic.
[0013] In one embodiment, the temperature of the hot pressing treatment is 500°C-1000°C, the pressure is 20MPa-60MPa, and the holding time is less than or equal to 300min.
[0014] In one of the embodiments, the annealing treatment temperature is 300°C-700°C, the heating rate is 1°C / min-10°C / min, and the holding time is less than or equal to 300 minutes.
[0015] In one embodiment, the hard carbon is selected from a material obtained by pre-carbonizing, removing impurities, pulverizing and carbonizing a hard carbon precursor.
[0016] In one embodiment, the hard carbon precursor is selected from at least one of a biomass substrate, a resin substrate, and an asphalt substrate;
[0017] And / or, the pre-carbonization temperature is 300°C-700°C, the heating rate is 1°C / min-10°C / min, and the holding time is less than or equal to 300min;
[0018] and / or, the median particle size of the particles after impurity removal and pulverization is 6 μm-12 μm;
[0019] And / or, the carbonization temperature is 1000°C-2000°C, the heating rate is 1°C / min-10°C / min, and the insulation time is less than or equal to 300 minutes.
[0020] A hard carbon negative electrode material prepared by the method for preparing the hard carbon negative electrode material as described above.
[0021] A negative electrode sheet prepared using the hard carbon negative electrode material as described above.
[0022] A secondary battery prepared using the negative electrode sheet as described above.
[0023] The preparation method described in the present invention comprises the following steps: mixing hard carbon with an inorganic carbon material having a specific compressive strength, and then sequentially performing hot pressing and annealing treatments. On the one hand, a specific amount of inorganic carbon material induces atomic rearrangement inside the hard carbon during the hot pressing process, changes the growth orientation and size of the internal microcrystals, and makes the grain size La reach above 12 nm, thereby effectively improving the hardness of the hard carbon negative electrode material. On the other hand, during the treatment process, not only physical cross-linking occurs between the hard carbon and the inorganic carbon material, thereby improving the density of the hard carbon negative electrode material, but also surface functional groups react to form a strong interface effect, which is beneficial to reducing interface side reactions, thereby improving the electrochemical properties and structural stability of the hard carbon negative electrode material.
[0024] Therefore, the preparation method described in the present invention is simple, efficient and low-cost, and the prepared hard carbon negative electrode material is used for the battery negative electrode, which can improve the cycle stability of the battery while ensuring the battery capacity. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0026] Figure 1 This is a Raman characterization curve of the hard carbon negative electrode material prepared in Example 2;
[0027] Figure 2 This is a Raman characterization curve of the hard carbon negative electrode material prepared in Comparative Example 1;
[0028] Figure 3 This is a scanning electron microscope image of a negative electrode sheet made of the hard carbon negative electrode material of Example 2;
[0029] Figure 4 This is a scanning electron microscope image of a negative electrode sheet made of the hard carbon negative electrode material of Comparative Example 1;
[0030] Figure 5 The first cycle charge and discharge curve of a sodium ion battery prepared using the hard carbon negative electrode material of Example 2;
[0031] Figure 6 The first cycle charge and discharge curve of a sodium ion battery prepared using the hard carbon negative electrode material of Comparative Example 1;
[0032] Figure 7 This is a curve chart of 15 cycles of a sodium ion battery prepared using the hard carbon negative electrode material of Example 2;
[0033] Figure 8This is a curve chart of 15 cycles of a sodium ion battery prepared using the hard carbon negative electrode material of Comparative Example 1. DETAILED DESCRIPTION
[0034] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0035] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific implementation methods or embodiments, and are not intended to limit the present invention. The optional scope of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the combinations include any two related listed items, any more related listed items, or all related listed items.
[0036] The present invention provides a method for preparing a hard carbon negative electrode material, comprising the following steps:
[0037] S1, mixing hard carbon and inorganic carbon material and performing hot pressing treatment, wherein the compressive strength of the inorganic carbon material is 200MPa-1000MPa, and the mass of the inorganic carbon material is 0.1%-1% of the mass of the hard carbon;
[0038] S2, annealing the product after the hot pressing treatment under an inert gas to obtain a hard carbon negative electrode material, wherein the grain size La of the hard carbon negative electrode material is greater than or equal to 12 nm.
[0039] In step S1, hard carbon is mixed with an inorganic carbon material having a specific compressive strength and then hot pressed. On the one hand, a specific amount of inorganic carbon material induces atomic rearrangement inside the hard carbon during the hot pressing process, changes the growth orientation and size of the internal crystallites, and makes the grain size La reach more than 12 nm, thereby effectively improving the hardness of the hard carbon negative electrode material. On the other hand, during the hot pressing process, the functional groups on the surface of the hard carbon and the inorganic carbon material, especially oxygen-containing functional groups such as hydroxyl (-OH), carboxyl (-COOH), carbonyl (-C=O), ester (-COOR), and aldehyde (-CHO), undergo oxidation-reduction, condensation, and hydrolysis reactions with each other, forming a strong interface effect, which is beneficial to reducing interface side reactions, thereby improving the electrochemical performance and stability of the hard carbon negative electrode material.
[0040] Wherein, the compressive strength of the inorganic carbon material includes but is not limited to any point value among 200MPa, 300MPa, 400MPa, 500MPa, 600MPa, 700MPa, 800MPa, 900MPa, 1000MPa or a range value between any two thereof.
[0041] The mass percentage of the inorganic carbon material includes but is not limited to any point value among 0.1%, 0.2%, 0.4%, 0.8%, 1% or any range value between the two.
[0042] Preferably, the Young's modulus of the inorganic carbon material is 50 GPa-700 GPa, including but not limited to any value among 50 GPa, 100 GPa, 200 GPa, 500 GPa, 700 GPa or a range between any two of them.
[0043] Preferably, the particle size of the inorganic carbon material is 10nm-100nm, including but not limited to any point value among 10nm, 20nm, 50nm, 60nm, 80nm, 100nm or any range value between two thereof, so that when the inorganic carbon material is mixed with hard carbon, it can fill the gaps in the hard carbon matrix material and undergo physical crosslinking during the hot pressing process, thereby improving the density of the hard carbon material and enhancing the bonding force between the carbon material particles, which is beneficial to further improve the structural stability of the hard carbon negative electrode material.
[0044] Preferably, the specific surface area of the inorganic carbon material is 800 m 2 / g-2000m 2 / g, including but not limited to 800m 2 / g、1000m 2 / g、1200m 2 / g、1500m 2 / g、1800m 2 / g, 2000m 2 Any point value in / g or any range of values between the two is beneficial to provide more additional contact points and interfaces to relieve stress, reduce the separation between particles under the action of external force, and thus improve the mechanical properties of hard carbon materials.
[0045] Specifically, the inorganic carbon material includes but is not limited to at least one of carbon fiber, graphene fiber, carbon nanotube, graphene or carbon ceramic.
[0046] In one embodiment, the temperature of the hot pressing treatment is 500° C.-1000° C.; the pressure is 20 MPa-60 MPa; and the holding time is less than or equal to 300 min.
[0047] It is to be understood that the present invention does not limit the source of hard carbon, and conventional commercial hard carbon products available on the market may be used, or homemade hard carbon may be used.
[0048] In one embodiment, the hard carbon is selected from a material obtained by pre-carbonizing, removing impurities, pulverizing and carbonizing a hard carbon precursor.
[0049] Preferably, the hard carbon precursor includes but is not limited to at least one of a biomass substrate, a resin substrate, and an asphalt substrate, wherein the biomass substrate includes a biomass starch material, a biomass coconut shell material, and a biomass bamboo material.
[0050] Preferably, the pre-carbonization temperature is 300°C-700°C, the heating rate is 1°C / min-10°C / min, and the holding time is less than or equal to 300 min.
[0051] Preferably, the median particle size of the particles after impurity removal and pulverization is 6 μm-12 μm, wherein the impurity removal includes steps such as acid washing, alkali washing, and water washing.
[0052] Preferably, the carbonization temperature is 1000°C-2000°C, the heating rate is 1°C / min-10°C / min, and the holding time is less than or equal to 300 min.
[0053] It is understandable that the above-mentioned pre-carbonization and carbonization are both carried out in an inert atmosphere, and the inert atmosphere includes but is not limited to nitrogen, argon, a hydrogen-nitrogen mixture, and a hydrogen-argon mixture.
[0054] In step S2, by conducting annealing treatment after hot pressing treatment, it is beneficial to eliminate internal stress, thereby further improving the structural stability of the hard carbon negative electrode material, significantly improving the hardness of the prepared hard carbon negative electrode material, enhancing the mechanical stability of the hard carbon negative electrode material, and at the same time enhancing the electrochemical properties of the hard carbon negative electrode material.
[0055] Specifically, the grain size La of the hard carbon negative electrode material includes but is not limited to any point value among 12nm, 15nm, 16nm, 18nm, 20nm, 22nm, 25nm, 30nm or a range value between any two of them, preferably 12nm-22nm.
[0056] In one embodiment, the annealing treatment is performed at a temperature of 300° C.-700° C., a heating rate of 1° C. / min-10° C. / min, and a holding time of less than or equal to 300 min.
[0057] It is understandable that the above annealing treatment is performed in an inert atmosphere, which includes but is not limited to nitrogen, argon, a hydrogen-nitrogen mixture, and a hydrogen-argon mixture.
[0058] The present invention provides a hard carbon negative electrode material prepared by the method for preparing the hard carbon negative electrode material as described above. The hard carbon negative electrode material has not only high hardness but also excellent electrochemical performance.
[0059] The present invention also provides a negative electrode sheet prepared by using the hard carbon negative electrode material as described above, and a secondary battery prepared by using the negative electrode sheet.
[0060] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer, and the negative electrode active material layer includes the hard carbon negative electrode material as described above. It can be understood that the secondary battery also includes a positive electrode sheet, a separator, and an electrolyte.
[0061] It should be noted that the present invention does not limit the preparation method of the negative electrode sheet, and a conventional process can be used. For example, the above-mentioned hard carbon negative electrode material and the binder are mixed in a mass ratio of 80:10-95:5 to form a slurry, which is coated on the current collector and dried. Among them, the binder includes but is not limited to at least one of sodium carboxymethyl cellulose, sodium alginate, and polyvinylidene fluoride, preferably sodium carboxymethyl cellulose. The solvent used to prepare the slurry is preferably water. The current collector includes copper foil or aluminum foil, the drying temperature is 60°C-120°C, and the drying time is 1h-20h.
[0062] The secondary battery includes a lithium ion battery and a sodium ion battery, preferably a sodium ion battery. Specifically, the electrolyte includes a sodium salt and a non-aqueous solvent, and the sodium salt includes but is not limited to at least one of NaPF6 and NaClO4, preferably NaPF6; the non-aqueous solvent includes but is not limited to at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate and diethyl carbonate, preferably a mixture of diethyl carbonate and ethylene carbonate.
[0063] The hard carbon negative electrode material, its preparation method and application will be further described below through the following specific examples. However, those skilled in the art will understand that the following examples are only used to illustrate the present invention and should not be regarded as limiting the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be obtained commercially.
[0064] It should be noted that the carbon ceramics used in the examples and comparative examples have a compressive strength of about 500 MPa, a Young's modulus of about 400 GPa, a particle size of about 100 nm, and a specific surface area of about 1500 m 2 / g; the compressive strength of carbon nanotubes is about 400MPa, the Young's modulus is about 600GPa, the particle size is about 80nm, and the specific surface area is about 1500m 2 / g.
[0065] Example 1
[0066] The biomass coconut shell material was pre-carbonized in a H2 / Ar mixed gas atmosphere, with a pre-carbonization temperature of 500°C, a heating rate of 5°C / min, and a carbonization time of 120min. The pre-carbonized material was treated with 2mol / L hydrochloric acid at 70°C for 5h, and then treated with 2mol / L sodium hydroxide solution at 70°C for 5h, filtered, washed, dried, and crushed to obtain a particle size D 50 The particles are 10 μm in size, passed through a 400-mesh sieve, and then subjected to high-temperature carbonization treatment in a N2 atmosphere at a temperature of 1400°C, a heating rate of 2°C / min, and a carbonization time of 120 min to obtain a hard carbon material.
[0067] The prepared hard carbon material and carbon ceramics are fully mechanically stirred and mixed, wherein the addition amount of carbon ceramics is 0.2% of the mass of the hard carbon material, and then the mixed material is subjected to high-temperature hot pressing treatment at a temperature of 500°C, a pressure of 20MPa, and a holding time of 120min.
[0068] The product after hot pressing treatment was heated to 500°C at a heating rate of 5°C / min under N2 atmosphere and kept at this temperature for 120 minutes, and then cooled to room temperature in the furnace to obtain a hard carbon negative electrode material.
[0069] Example 2
[0070] The hard carbon material was prepared by the same method as in Example 1.
[0071] The prepared hard carbon material and carbon ceramics are fully mechanically stirred and mixed, wherein the addition amount of carbon ceramics is 0.4% of the mass of the hard carbon material, and then the mixed material is subjected to high-temperature hot pressing treatment at a temperature of 700°C, a pressure of 40MPa, and a holding time of 120min.
[0072] The product after hot pressing treatment was heated to 600°C at a heating rate of 5°C / min under N2 atmosphere and kept at this temperature for 120 minutes, and then cooled to room temperature in the furnace to obtain a hard carbon negative electrode material.
[0073] Example 3
[0074] The hard carbon material was prepared by the same method as in Example 1.
[0075] The prepared hard carbon material and carbon ceramics are fully mechanically stirred and mixed, wherein the addition amount of carbon ceramics is 0.6% of the mass of the hard carbon material, and then the mixed material is subjected to high-temperature hot pressing treatment at a temperature of 1000°C, a pressure of 60MPa, and a holding time of 120min.
[0076] The product after hot pressing treatment was heated to 700°C at a heating rate of 5°C / min under N2 atmosphere and kept at this temperature for 120 minutes, and then cooled to room temperature in the furnace to obtain a hard carbon negative electrode material.
[0077] Example 4
[0078] The biomass bamboo material was pre-carbonized in a H2 / Ar mixed gas atmosphere, with a pre-carbonization temperature of 700°C, a heating rate of 10°C / min, and a carbonization time of 120min. The pre-carbonized material was treated with 2mol / L hydrochloric acid at 70°C for 5h, and then treated with 2mol / L sodium hydroxide solution at 70°C for 5h, filtered, washed, dried, and crushed to obtain a particle size D 50 The particles are 10 μm in size, passed through a 400-mesh sieve, and then subjected to high-temperature carbonization treatment in a N2 atmosphere at a temperature of 1400°C, a heating rate of 2°C / min, and a carbonization time of 120 min to obtain a hard carbon material.
[0079] The prepared hard carbon material and carbon nanotubes are fully mechanically stirred and mixed, wherein the addition amount of carbon nanotubes is 0.4% of the mass of the hard carbon material, and then the mixture is subjected to high-temperature hot pressing treatment at a temperature of 600°C, a pressure of 40MPa, and a holding time of 180min.
[0080] The product after hot pressing treatment was heated to 500°C at a heating rate of 5°C / min under N2 atmosphere and kept at this temperature for 120 minutes, and then cooled to room temperature in the furnace to obtain a hard carbon negative electrode material.
[0081] Example 5
[0082] The hard carbon material was prepared by the same method as in Example 4.
[0083] The prepared hard carbon material and carbon nanotubes are fully mechanically stirred and mixed, wherein the addition amount of carbon nanotubes is 0.6% of the mass of the hard carbon material, and then the mixture is subjected to high-temperature hot pressing treatment at a temperature of 600°C, a pressure of 55MPa, and a holding time of 180min.
[0084] The product after hot pressing treatment was heated to 500°C at a heating rate of 5°C / min under N2 atmosphere and kept at this temperature for 120 minutes, and then cooled to room temperature in the furnace to obtain a hard carbon negative electrode material.
[0085] Example 6
[0086] The difference between Example 6 and Example 1 is that the added amount of carbon ceramic is 1.0% of the mass of the hard carbon material.
[0087] Comparative Example 1
[0088] The biomass coconut shell material was pre-carbonized in a H2 / Ar mixed gas atmosphere, with a pre-carbonization temperature of 500°C, a heating rate of 5°C / min, and a carbonization time of 120min. The pre-carbonized material was treated with 2mol / L hydrochloric acid at 70°C for 5h, and then treated with 2mol / L sodium hydroxide solution at 70°C for 5h, filtered, washed, dried, and crushed to obtain a particle size D 50 The particles were 10 μm in size and passed through a 400-mesh sieve. They were then subjected to high-temperature carbonization treatment in a N2 atmosphere at a temperature of 1400°C, a heating rate of 2°C / min, and a carbonization time of 120 min to obtain a hard carbon negative electrode material.
[0089] Comparative Example 2
[0090] The biomass bamboo material was pre-carbonized in a H2 / Ar mixed gas atmosphere, with a pre-carbonization temperature of 700°C, a heating rate of 10°C / min, and a carbonization time of 120min. The pre-carbonized material was treated with 2mol / L hydrochloric acid at 70°C for 5h, and then treated with 2mol / L sodium hydroxide solution at 70°C for 5h, filtered, washed, dried, and crushed to obtain a particle size D 50 The particles were 10 μm in size and passed through a 400-mesh sieve. They were then subjected to high-temperature carbonization treatment in a N2 atmosphere at a temperature of 1400°C, a heating rate of 2°C / min, and a carbonization time of 120 min to obtain a hard carbon negative electrode material.
[0091] Comparative Example 3
[0092] The difference between Comparative Example 3 and Example 2 is that the mixed material is subjected to high temperature treatment but not to pressure treatment.
[0093] Comparative Example 4
[0094] The difference between Comparative Example 4 and Example 2 is that the mixed material is subjected to pressure treatment at a pressure of 40 MPa for a holding time of 120 min without heating.
[0095] Comparative Example 5
[0096] The difference between Comparative Example 5 and Example 2 is that no annealing treatment is performed, and the product after hot pressing treatment is used as a hard carbon negative electrode material.
[0097] Comparative Example 6
[0098] The difference between Comparative Example 6 and Example 2 is that conductive carbon black (compression strength of 150 MPa) is used instead of carbon ceramics.
[0099] The hard carbon negative electrode materials prepared in Examples 1-6 and Comparative Examples 1-6 were tested. The results are as follows: Figure 1-8 And as shown in Table 1.
[0100] (1) Raman test: Raman characterization is performed to further analyze the microstructural changes of carbon materials. The grain size La is further calculated by the Tuinstra-Koenig equation = (2.4 × 10 -10 ) 4 (I D / I G ) -1 , where λ=532nm, the G peak represents the graphitization degree of the carbon material, that is, the change in internal crystallinity, and the D peak represents the defect degree of the carbon material, that is, the degree of internal disorder.
[0101] (2) Hardness test: The Vickers hardness test method is used to test the hardness of hard carbon materials. The hardness of hard carbon materials is determined by applying the same pressure and measuring the diagonal length of the indentation on the surface of the material. According to the formula HV = 1.8544 × F / d 2 Calculate the hardness, where HV is the Vickers hardness, F is the applied pressure, and d is the average diagonal length of the indentation. Before the test, various hard carbons were pressed at 40MPa and an external force of 200kg was applied to the pressed tablets for testing, of which 9.8kgf / mm 2 =1MPa.
[0102] (3) Performance test: Weigh 141 mg of hard carbon negative electrode material and 9 mg of carboxymethyl cellulose, add appropriate amount of deionized water and use planetary ball mill for 2 hours, apply the milled slurry on the current collector, dry it in vacuum at 100 ° C for 12 hours, and cut it into negative electrode sheets with a diameter of 12 mm. Use metallic sodium as the counter electrode and reference electrode, use glass fiber diaphragm as the diaphragm, use NaPF6 with a concentration of 1 mol / L as the electrolyte, and use a mixed solution of diethyl carbonate and ethylene carbonate (volume ratio of 1:1) as the solvent. Assemble button cells in a glove box with argon atmosphere. The electrochemical performance of the prepared button cells was tested on the Xinwei battery test system. The charge and discharge voltage range was 0-2V, the current density was 0.5C, and 1C = 100mA / g.
[0103] Table 1
[0104]
[0105]
[0106] According to Table 1, the grain size of the hard carbon negative electrode material prepared in Examples 1-6 is about 13nm-30nm, the hardness is greatly improved, and the charge-discharge specific capacity and 100-cycle capacity retention rate can maintain a high performance effect. In addition, by comparing Example 1 with Example 6, it can be seen that when the amount of inorganic carbon material is increased to 1%, due to the excessive proportion of ordered carbon material components, the hardness of the hard carbon negative electrode material will be too large, which is not conducive to the insertion and extraction of sodium ions, thereby causing electrical performance degradation.
[0107] However, Comparative Examples 1 and 2 use traditional carbonization methods, resulting in low hardness and poor structural stability of the hard carbon negative electrode material. During the charge and discharge process, the structure of the material is easily damaged, making it difficult to maintain a long cycle life and a high coulombic efficiency; Comparative Example 3 does not perform pressurization treatment simultaneously with the heating treatment, and Comparative Example 4 does not perform heating treatment simultaneously with the pressurization treatment, which will lead to insufficient growth of internal microcrystals, resulting in low hardness and poor electrical properties of the hard carbon negative electrode material; Comparative Example 5 does not undergo annealing treatment, and due to the existence of internal stress, it has poor stability.
[0108] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0109] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a hard carbon negative electrode material, characterized in that: The steps include: Mixing hard carbon and inorganic carbon material and subjecting them to hot pressing treatment, wherein the compressive strength of the inorganic carbon material is 200MPa-1000MPa, and the mass of the inorganic carbon material is 0.1%-1% of the mass of the hard carbon; The product after the hot pressing treatment is annealed under an inert gas to obtain a hard carbon negative electrode material, wherein the grain size La of the hard carbon negative electrode material is greater than or equal to 12 nm.
2. The method for preparing a hard carbon negative electrode material according to claim 1, characterized in that: The grain size La of the hard carbon negative electrode material is 12nm-22nm; And / or, the Young's modulus of the inorganic carbon material is 50 GPa-700 GPa; And / or, the particle size of the inorganic carbon material is 10nm-100nm; And / or, the specific surface area of the inorganic carbon material is 800m 2 / g-2000m 2 / g.
3. The method for preparing a hard carbon negative electrode material according to claim 1 or 2, characterized in that: The inorganic carbon material is selected from at least one of carbon fiber, graphene fiber, carbon nanotube, graphene or carbon ceramic.
4. The method for preparing a hard carbon negative electrode material according to claim 1, characterized in that: The temperature of the hot pressing treatment is 500° C.-1000° C., the pressure is 20 MPa-60 MPa, and the holding time is less than or equal to 300 minutes.
5. The method for preparing a hard carbon negative electrode material according to claim 1, characterized in that: The annealing treatment temperature is 300° C.-700° C., the heating rate is 1° C. / min-10° C. / min, and the holding time is less than or equal to 300 min.
6. The method for preparing a hard carbon negative electrode material according to claim 1, characterized in that: The hard carbon is selected from a material obtained by pre-carbonizing, removing impurities, pulverizing and carbonizing a hard carbon precursor.
7. The method for preparing a hard carbon negative electrode material according to claim 6, characterized in that: The hard carbon precursor is selected from at least one of a biomass substrate, a resin substrate, and an asphalt substrate; And / or, the pre-carbonization temperature is 300°C-700°C, the heating rate is 1°C / min-10°C / min, and the holding time is less than or equal to 300min; and / or, the median particle size of the particles after impurity removal and pulverization is 6 μm-12 μm; And / or, the carbonization temperature is 1000°C-2000°C, the heating rate is 1°C / min-10°C / min, and the insulation time is less than or equal to 300 min.
8. A hard carbon negative electrode material obtained by the method for preparing a hard carbon negative electrode material according to any one of claims 1 to 7.
9. A negative electrode sheet prepared using the hard carbon negative electrode material as claimed in claim 8.
10. A secondary battery prepared using the negative electrode sheet as claimed in claim 9.